The Implications of Parental Role Involvement on the Development of Primary School Students' Spiritual Intelligence - Ahmad; Sularsih; Janti Murdiani; Darsinah; Murfiah Dewi Wulandari (Elementary Teacher Education Program, Majalengka University, 2025)
This research purpose is to analyse the implications of parental involvement on the development of elementary school students' spiritual intelligence. The active role of teachers in activities involving parents is a strategic step for teachers in maximising the process of education and spiritual development of students. The qualitative method involving a field approach was used in this study. Then participatory observation, in-depth interviews and documentation analysis were used to collect data and analyse the data using the stages of analysis developed by Miles & Huberman. The result is that teachers at SD Negeri Nganti Gemolong always try to provide a good and impactful educational process through learning patterns that emphasise the development of students' spiritual intelligence such as Islamic boarding school, Jumanji (Jumaat mengaji). Then the active role of parents through involvement in every child's activities at school is one of the factors that significantly encourage the development of children's spiritual intelligence. The implication for children is that they are able to understand and implement the content of spiritual intelligence such as, obeying worship, tolerance, honouring parents, honesty and behaviour that reflects akhlakul karimah. It is hoped that further research will develop extracurricular programmes that are oriented towards the development of students' spiritual intelligence by involving parents.